2013
DOI: 10.4161/hv.22415
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors potentially associated with mumps transmission in Yeshivas during a mumps outbreak among highly vaccinated students: Brooklyn, New York, 2009–2010

Abstract: (2013) Environmental factors potentially associated with mumps transmission in Yeshivas during a mumps outbreak among highly vaccinated students: Brooklyn, New York,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 14 publications
(20 reference statements)
0
14
0
Order By: Relevance
“…In this outbreak, mumps transmission was associated with intense contact among students in religious schools, similar to the preceding outbreak in New York. 7,25 Nevertheless, the clinical disease was significantly milder among vaccinated cases. Probable contributing factors to the outbreak include insufficient vaccine effectiveness and less than optimal vaccination coverage.…”
Section: Discussionmentioning
confidence: 99%
“…In this outbreak, mumps transmission was associated with intense contact among students in religious schools, similar to the preceding outbreak in New York. 7,25 Nevertheless, the clinical disease was significantly milder among vaccinated cases. Probable contributing factors to the outbreak include insufficient vaccine effectiveness and less than optimal vaccination coverage.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Using a Poisson regression analysis and a case-crossover methodology, we analyzed mumps data reported to the Taiwan CDC from 2006 to 2011. We found that the incidence of mumps was highest during the summer months but that incidence was positively correlated with increased mean temperature and vapor pressure in both the long-term and acute effect analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Mumps attack rates above 10% among vaccinated university students have been reported during various recent outbreaks [ 5 , 6 ]. Those attack rates were based on a particular setting within a specific time frame, and they are therefore probably higher than overall attack rates in a nationwide outbreak.…”
mentioning
confidence: 99%